دور أنشطة اللوجستيك في تعزيز استراتيجية التميز: دراسة استطلاعية لآراء عينة من العاملين في الشركة العامة للصناعات الكهربائية / ديالي - المتيوتي، محمد أحمد محمود; صالح، شوكت خالد; حنظل، قاسم أحمد (جامعة كركوك - كلية الإدارة والاقتصاد, 2020)
تهدف الدراسة إلى التعرف على أنشطة اللوجستيك ومدى التزام الشركة المبحوثة بها لضمان تعزيز استراتيجية التميز للشركة. وتم وضع فرضيات الدراسة تحقيقا لمقاصدها وتوجهاتها، ووزعت (70) استمارة استبانة على العاملين في الشركة العامة للصناعات الكهربائية / ديالى، وجرى اختبار فرضيات الدراسة باستخدام تحليل الارتباط والتباين لتشخيص علاقات الارتباط والأثر بين المتغيرات المبحوثة، وخلصت الدراسة إلى مجموعة من الاستنتاجات لعل من أهمها. تحقق وجود تأثير معنوي موجب لمتغيرات أنشطة الخدمات اللوجستية في أبعاد استراتيجية التميز في الشركة المبحوثة، فضلا عن تقديم مجموعة من المقترحات أهمها: زيادة اهتمام الشركة المبحوثة بأنشطة الخدمات اللوجستية وأبعاد استراتيجية التميز لما لهما من دور في تحقيق الميزة التنافسية للشركة.
The study aims to identify the Allojcetk activities and the extent of the company surveyed its commitment to ensure the promotion of excellence strategy for the company It was developed hypotheses of the study achieve its purposes and orientations, and distributed (70) questionnaire on the staff of the General Company for Electrical Industries / Diyala form, was hypotheses were tested using correlation analysis and contrast for the diagnosis of correlation and impact between the researched variables, and the study found a set of conclusions, most notably .Check the existence of a significant positive impact to the variables of logistics activities in the dimensions of Excellence strategy in the company researched 0, as well as providing a set of proposals, including: Increase the interest of the company surveyed logistics activities and dimensions of excellence due to their role in achieving the competitive advantage of the company's strategy.
Keywords: الإدارة الاستراتيجية -- الميزة التنافسية -- إدارة الموارد البشرية -- المؤسسات الصناعية -- العراق